Occurrence of Pathogenic Bacteria (Coliform, Escherichia coli, and Salmonella) in Dried Anchovies (Stolephorus sp.) from Traditional Markets in Ternate City, North Maluku Province, Indonesia - Mahmud Hasan (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
Dried anchovies (Stolephorus sp.) are widely consumed in Indonesia due to their affordability, nutritional value, and availability in traditional markets. However, as a dried fish product, they are highly susceptible to microbial contamination if not properly handled, which may compromise food safety and consumer health. Pathogenic bacteria such as Coliform, Escherichia coli, and Salmonella are among the most concerning contaminants, as their presence in food products can cause gastrointestinal illnesses ranging from nausea, vomiting, and fever to severe outcomes. This study aimed to determine the presence of pathogenic bacteria in dried anchovy samples obtained from three traditional markets in Ternate City, North Maluku Province Bastiong, Kie Raha, and Dufa-Dufa. Microbiological analyses were conducted using Total Plate Count (TPC), Coliform, Escherichia coli, and Salmonella tests, with reference to the Indonesian National Standard (SNI). The results indicated that microbial counts were far below the rejection threshold, and the pathogenic bacteria tested were all negative. These findings suggest that dried anchovies sold in the three markets remain safe and suitable for consumption, although continuous monitoring and proper handling practices are recommended to maintain product quality and food safety.